Pengelolaan arsip dinamis inaktif elektronik melalui aplikasi SIKD (Sistem Informasi Kearsipan Dinamis) dan hambatannya di Dinas Perpustakaan - Ratna Anugraheni Putri; I Nyoman Suputra (Universitas Negeri Malang, 2022)
One of the electronic media in archive management is SIKD usage. This SIKD application focuses on managing inactive dynamic records more quickly and practically. This research aims to serve evaluation results in a scientific narrative description of the process of management activities, advantages and disadvantages, effectiveness of managing electronic inactive archives through SIKD and obstacles arise. This research uses a qualitative method with a descriptive evaluative approach. The data collection technique used is through observation, interviews and documentation studies as well as determining the sample using purposive sampling. While the data analysis techniques applied were data collection, data reduction, data presentation, and data verification also calculating the effectiveness of archive retrieval by the formula archives accuracy number. From the research, researcher found that archive management through applications contained in this institution was not completely electronic based so that there were still archive activities that had to collaborate in completing conventional archive management. These actions, eventually found that hampered the smooth work of archivists as well as the need for employee empowerment and accommodation of the institution work system to be adjusted and refined again for better archive management in the future. Media elektronik dalam pengelolaan arsip salah satunya yaitu penggunaan aplikasi Sistem Informasi Kearsipan Dinamis (SIKD). Aplikasi ini berfokus untuk pengelolaan arsip dinamis inaktif yang cepat dan praktis. Penelitian ini bertujuan untuk medeskripsikan proses kegiatan pengelolaan, kelebihan dan kekurangan, efektivitas serta hambatan yang muncul. Penelitian ini menggunakan pendekatan kualitatif evaluatif deskriptif. Teknik pengumpulan data yang digunakan yakni melalui observasi, wawancara serta dokumentasi. Penentuan sampel menggunakan purposive sampling. Analisis data yang diterapkan yakni pengumpulan data, reduksi data, penyajian data, dan verifikasi data serta penghitungan efektivitas temu balik arsip dengan rumus angka kecermatan arsip. Dari proses penelitian bahwa pengelolaan arsip melalui aplikasi yang terdapat pada instansi ini belum seutuhnya berbasis elektronik sehingga masih terdapat kegiatan arsip yang harus berkolaborasi dalam menyelesaikan manajemen arsip secara konvensional. Tindakan tersebut, akhirnya juga ditemui hal yang menghambat sehingga berdampak pada kelancaran kerja arsiparis serta perlunya pemberdayaan pegawai dan pengakomodiran sistem kerja instansi untuk disesuaikan dan disempurnakan kembali agar lebih baik pengelolaan arsip kedepannya